Measurement of photoneutron fluxes on the processing table of two VARIAN IX medical linear accelerators (Damascus University Journal for the basic sciences, 2025)
In this research, the fluxes of optical neutrons accompanying the high-energy photon beams 18 MV and 23 MV issued by the two VARIAN IX medical linear accelerators available at Tishreen University Hospital in Lattakia, Radiation Treatment Division, were measured.40 CR-39 detectors were installed on wooden beams in succession and at a stepof 50 cm to measure the optical neutron fluxes. These detectors were distributed transversely and longitudinally on the processing table of each linear accelerator. The irradiation field of the accelerator was used with dimensions of 40´40 cm2 and the distance was adjusted from the accelerator head to the surface of the treatment table should be SSD=100cm. The measurement results indicated that the value of the photoneutron flux is:→ It is highest in the center of the irradiation field, where the value reached 5.0 x 108  n/(cm2.Gy)   for the 23 MV beam and 4.8 x 108  n/(cm2.Gy)   for the 18 MV beam.→ - It decreases in a Gaussian symmetry with respect to the horizontal axis passing through the center of the irradiation square→ - In the case of the 23 MV package, it exceeds that of the18 MV package by 17%.
Keywords: Photoneutrons; neutron flux; CR-39 detectors; linear accelerator; high energy photon beams